2005
DOI: 10.1002/adfm.200305146
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Electroluminescence Color in Polymer Light-Emitting Devices Using the Thiol-Ene Photoreaction

Abstract: Laterally patterning the emission color of polymer light‐emitting devices is one of the current technological challenges for their commercialization. Photopatterning is one of the most convenient approaches for the production of closely spaced, differently colored pixels, other than direct‐writing approaches such as ink‐jet printing. The photo‐induced addition of thiols to CC bonds (the thiol‐ene) reaction is here utilized to achieve photobleaching of poly(phenylenevinylene)‐type polymers. By exploiting the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 32 publications
1
28
0
3
Order By: Relevance
“…Heck coupling has become an important method to construct molecules and polymers,24 such as luminescent molecules25 and conjugated polymers,26 as well as SQ derivatives 27. More importantly, this method can preserve the double bonds, which can act as useful active groups for post‐functionalization that would endow the resulting materials with novel functionalities 28. However, to the best of our knowledge, reports on the exploitation of SQ‐based azobenzene derivatives through the Heck cross‐coupling, which could extend the length of the conjugated structure of the azobenzene unit by introduction of ethenylene, are not available to date.…”
Section: Introductionmentioning
confidence: 99%
“…Heck coupling has become an important method to construct molecules and polymers,24 such as luminescent molecules25 and conjugated polymers,26 as well as SQ derivatives 27. More importantly, this method can preserve the double bonds, which can act as useful active groups for post‐functionalization that would endow the resulting materials with novel functionalities 28. However, to the best of our knowledge, reports on the exploitation of SQ‐based azobenzene derivatives through the Heck cross‐coupling, which could extend the length of the conjugated structure of the azobenzene unit by introduction of ethenylene, are not available to date.…”
Section: Introductionmentioning
confidence: 99%
“…[4] In a similar fashion, this process can be applied to derivatives of PPV where the C --C bonds are partly hydrosilylated and partly hydrogenated. [5] Another approach is based upon the thiol-ene reaction: in a radical-mediated reaction, thiols are readily added to C --C groups both in elastomers [6] and derivatives of PPV [7] to give polymers functionalized with alkylthio substituents. Also hydrazine has been found to be a useful reagent for the modification of unsaturated polymers.…”
Section: Full Papermentioning
confidence: 99%
“…However, due to strong solute–water (H 2 O) interaction between the adsorbent and wastewater, the adsorption capability of CMPs for hydrophilic solutes, such as H 2 O‐soluble dye and metal iron, is reduced. Therefore, ways have been developed to turn monomers microstructures of the materials or develop their surface oleophilicity and hydrophobility by modifying some hydrophilic groups for wastewater treatment . For example, Han et al reported N ‐acetylcysteine (NAC)‐modified CMPs through a thiol‐yne click reaction, which were found to have good adsorption capacity for separation of uranium from radioactive effluents because of the improved hydrophilic nature.…”
Section: Introductionmentioning
confidence: 99%